IMPLEMENTASI HAK UJI MATERIIL PERATURAN DAERAH KABUPATEN/KOTA OLEH MAHKAMAH AGUNG DAN PENGARUHNYA TERHADAP PEMBERDAYAAN DAERAH - AbdulAziz Nasihuddin (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Legislation set two mechanisms of review or oversight of local regulations, the executive and ju-dicial review. Executive authority to oversee the review of local regulations is owned by the govern-ment (executive power), while the judicial review of the authority overseeing local regulation held by the Supreme Court (judicial power). Both of these mechanisms may lead to the cancellation rules of the regulation is contrary regional.Research districts/cities were canceled by the Minister of domestic affairs who then filed a judicial review to the Supreme Court and its effect on empower-ment regional. Approach used are normative and case studies. Secondary data to primary data.Data were collected by the research literature and several areas as places research. Result research shows that the implementation of the right of judicial review of Regulation Regency/negative effect on local empowerment. Key words: supervision, regulation rights judicial region, regional empowerment